Efeito da L-tiroxina sódica na tolerância ao esforço e no perfil lipídico em mulheres com hipotireoidismo subclínico - Gonçalves, Alexandre (2005)
Several studies have associated subclinical hypothyroidism with risk factors for atherosclerotic disease, but its correlation with a decreased tolerance to the physical effort has been little studied. In this context, the hormonal replacement with L-thyroxine for the treatment of these patients remains controversial. The present study aimed to analyze the effect of sodium L-thyroxine on the tolerance to the physical effort and the lipidic profile of patients with subclinical hypothyroidism. Seven female volunteers aged between 40 and 60 years, without clinical signs of hypothyroidism and with TSH > 4.4 mU/dL, total T3 and free T4 in the plasma were selected. The plasmatic lipidic profile was evaluated before and after treatment of all patients. For the evaluation of tolerance to the physical effort, all patients were submitted to a progressive effort test. Levels of blood lactate before and after treatment were analyzed as parameters of effort. There was a significant improvement in tolerance to the lactate and consequently, in tolerance to the effort after treatment with thyroxine. The results demonstrated a significant decrease of LDL-c and triglycerides after the normalization of TSH levels with the hormonal replacement. Significant differences were not observed in the levels of HDL, VLDL and total cholesterol.